Algoritma Berhitung Blija ̂h: Alternatif Pembelajaran Operasi Penjumlahan dan Pengurangan - Loviga Denny Pratama; Wahyu Setyaningrum (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
The aim of this study was to describe arithmetic algorithm on transaction employed by Blij h. The study was a qualitative approach by means of case study in Madurese community. The data were gathered through observation and interviews. The partisipants of this study were 8 Blij h living in Paiton, Probolinggo. The data were analyzed using Miles & Huberman model. The results of this study obtained some arithmatics algorithm of addition, subtraction, multipication, and division. This paper, however, will only focus on addition and subtraction algorithm. The data reveals that there are several differences in the algorithm used by Blij h and the one taught at school. The results of this study could be used as one of teaching and learning approach to develop numerical and mental calculation skills.